2010
DOI: 10.1097/pas.0b013e3181e02f45
|View full text |Cite
|
Sign up to set email alerts
|

Triple Negative Breast Cancer: Outcome Correlation With Immunohistochemical Detection of Basal Markers

Abstract: We earlier evaluated the relationship of 653 triple negative breast cancers (TNBC) with basal immunophenotypic expression by using antibodies to basal cytokeratins (CK5/6, CK14, CK17, 34betaE12), p63, smooth muscle actin (SMA), epidermal growth factor receptor, and CD117, and found that a triple panel of CK14, 34betaE12 and epidermal growth factor receptor determined 84% of our cases to be basal-like. Women with basal-like TNBC tended to be younger (P=0.04), have histologically higher-grade tumors (P=0.047), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 39 publications
7
68
2
Order By: Relevance
“…19 Despite the different definitions for basal-like breast cancers, it has been demonstrated that these tumors have distinctive clinical presentations, 20 histological features, 18,21 response to chemotherapy, [22][23][24][25][26][27][28] sites of distant relapse, and outcome. 7,9,[29][30][31] In brief, basal-like tumors comprise a heterogeneous group that accounts for up to 15% of all breast cancers, affect younger patients, are more prevalent in African-American women, and often present as interval cancers. Histologically, the majority of basal-like breast cancers is of IDC-NST type, high histological grade, and characterized by exceptionally high mitotic indices, the presence of central necrotic or fibrotic zones, pushing borders, conspicuous lymphocytic infiltrate, and typical/atypical medullary features ( Figure 1).…”
Section: What Is a Basal-like Breast Cancer?mentioning
confidence: 99%
See 1 more Smart Citation
“…19 Despite the different definitions for basal-like breast cancers, it has been demonstrated that these tumors have distinctive clinical presentations, 20 histological features, 18,21 response to chemotherapy, [22][23][24][25][26][27][28] sites of distant relapse, and outcome. 7,9,[29][30][31] In brief, basal-like tumors comprise a heterogeneous group that accounts for up to 15% of all breast cancers, affect younger patients, are more prevalent in African-American women, and often present as interval cancers. Histologically, the majority of basal-like breast cancers is of IDC-NST type, high histological grade, and characterized by exceptionally high mitotic indices, the presence of central necrotic or fibrotic zones, pushing borders, conspicuous lymphocytic infiltrate, and typical/atypical medullary features ( Figure 1).…”
Section: What Is a Basal-like Breast Cancer?mentioning
confidence: 99%
“…The main characteristics of triple-negative cancers that have emerged from the literature illustrate their similarities to basal-like cancers, including the fact that they more frequently affect younger patients (o50 years), 24,30,31,59,61,62 are more prevalent in African-American women, [62][63][64] often present as interval cancers, and are significantly more aggressive than tumors of other molecular subtypes. 24,28,59,[61][62][63] This aggressiveness is best exemplified by the fact that the peak risk of recurrence is between the first and third years and the majority of deaths occur in the first 5 years following therapy.…”
Section: S Badve Et Almentioning
confidence: 99%
“…20 To define basal-like triple-negative breast cancer, we applied a tri-panel of CK14, EGFR and 34bE12 with 100% specificity and 78% sensitivity as documented in our previous studies. 21,22 …”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Using each of the 9 markers for TNT would increase the share of basal-like tumors to up to 94% and this would include those that are not in correlation with the results obtained by the only valid gene expression analysis. Generally speaking, increasing the number of markers increases the test specificity and sensitivity 10 . However, as there is no general consensus on the criteria for identifying basal-like tumors through immunohistochemical analysis, it is recommendable to use a limited number of markers, such as CK 5/6, CK 14, CK 17, P-cadherin and EGFR 5,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking, an increase in the number of markers increases test specificity and sensitivity 10 . However, as there is no such consensus on the criterion for identifying basal like tumors through immunohistochemical analysis, it is recommendable to use a limited number of markers, such as: CK 5/6, CK 14, CK 17, P-cadherin and EGFR 5,11 .…”
Section: Lesar Et Almentioning
confidence: 99%